The Japanese numbers game : the use and understanding of numbers in modern Japan - Crump, Thomas (Nissan Institute/Routledge Japanese studies series., 1992)
An almost obsessional use of numbers characterizes Japanese popular culture. A wide variety of numerical formulae and strategies provide the means for explaining events and solving problems occurring in everyday life. These include such matters as the choice of the name for a child, ranking in almost any game or sport, the diagnosis and cure of illness or the decision to accept a new job. This text provides a general study of the field of Japanese popular numeracy. It introduces the reader to a world of numbers in which fortune-telling, the abacus and games involving numbers, as well as cur.